Carbon assimilation and losses during an ocean acidification mesocosm experiment, with special reference to algal blooms. (August 2017) - Liu, Nana; Tong, Shanying; Yi, Xiangqi; Li, Yan; Li, Zhenzhen; Miao, Hangbin; Wang, Tifeng; Li, Futian; Yan, Dong; Huang, Ruiping; Wu, Yaping; Hutchins, David A.; et al.
Abstract: A mesocosm experiment was conducted in Wuyuan Bay (Xiamen), China, to investigate the effects of elevated p CO2 on bloom formation by phytoplankton species previously studied in laboratory-based ocean acidification experiments, to determine if the indoor-grown species performed similarly in mesocosms under more realistic environmental conditions. We measured biomass, primary productivity and particulate organic carbon (POC) as well as particulate organic nitrogen (PON). Phaeodactylum tricornutum outcompeted Thalassiosira weissflogii and Emiliania huxleyi, comprising more than 99% of the final biomass. Mainly through a capacity to tolerate nutrient-limited situations, P. tricornutum showed a powerful sustained presence during the plateau phase of growth. Significant differences between high and low CO2 treatments were found in cell concentration, cumulative primary productivity and POC in the plateau phase but not during the exponential phase of growth. Compared to the low p CO2 (LC) treatment, POC increased by 45.8–101.9% in the high p CO2 (HC) treated cells during the bloom period. Furthermore, respiratory carbon losses of gross primary productivity were found to comprise 39–64% for the LC and 31–41% for the HC mesocosms (daytime C fixation) in phase II. Our results suggest that the duration and characteristics of a diatom bloom can be affected by elevated p CO2 . Effects of elevated p CO2 observed in the laboratory cannot be reliably extrapolated to large scale mesocosms with multiple influencing factors, especially during intense algal blooms. Highlights: CO2 enrichment mesocosm experiments were performed in the Chinese coastal water. Elevated p CO2 enhanced the carbon fixation of phytoplankton during blooming period. Phaeodactylum tricornutum dominated the biomass after nutrient depletion.